Poor coordination among government departments and Border Control Agencies : its impact on South African Porous Borders - Malatji, T. L. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
This paper is focusing on the challenges of border control and coordination which are experienced by some of the government departments and agency in South Africa. This is a conceptual paper which the author relied mostly on secondary data. The South African borders are managed by several departments and government agency such as the Department of Home Affairs which is taking the lead, South African Police Service (SAPS) South African National Defence Force (SANDF), Department of Transport, Department of Environmental Affairs, Department of Agriculture, Department of Health and South African Receiver of Revenue (SARS, Customs). All these departments have different command structures with different aims, work ethics and mandates. At some border posts, departments are housed in disconnected buildings and this continue to make sharing of information impossible. There is no institutional mechanism that provides for accountability of the various departments and their agencies, and there is no platform that links their information or IT systems. The paper concludes that good coordination should be taken into account when addressing the issues of border management in South Africa. Keywords: Coordinated border management, Customs, Immigration, Integration, Porosity
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Coordinated border management; Customs; Immigration; Integration; Porosity; Border security -- South Africa; Emigration and immigration; Porosity